Two new records of the genus Hydryphantes (Acari: Hydrachnidia) for the Turkish Fauna - Esen, Yunus; Mart, Abdullah; Erman, Orhan (My University, 2019)
Two species of the genus Hydryphantes Koch, 1841 collected from Bayburt and BingölProvinces, Hydryphantes (s.str.) armentarius Gerecke, 1996 and H. (s.str.) fontinalis Sokolow, 1936 are given as new records for the Turkishfauna.
Keywords: Biyoloji; Entomoloji